2018
DOI: 10.9734/ejmp/2018/45129
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic Activity of Convallatoxin Isolated from the Root Bark of Parquetina nigrescens (Afzel.) Bullock (Asclepiadaceae)

Abstract: This study investigated the anti-diabetic activity of the root bark extract of Parquetina nigrescens and the isolated compound, convallatoxin, from the root bark. A powdered sample of the plant was extracted with methanol, and the extract (A) was tested in glucose-loaded normal rats at 100, 200 and 400 mg/kg for the determination of the most active dose. The anti-diabetic activity of A at 200 mg/kg was carried out on streptozotocin-induced diabetic rats. A was further partitioned to obtain its n-hexane (B 1 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The extract at100, 200 and 400 mg/kg was devoid of activity at 0.5-2 h but at 4 h it showed hyperglycaemia lowering effect comparable to glibenclamide (5 mg/kg) thus indicating only insulin stimulation as its mechanism of action (Table 1). Similar effects have been reported for the extracts of Parquetina nigrescens and Uvaria afzelii [26,31].…”
Section: Glucose Lowering Activity Of the Extractsupporting
confidence: 87%
“…The extract at100, 200 and 400 mg/kg was devoid of activity at 0.5-2 h but at 4 h it showed hyperglycaemia lowering effect comparable to glibenclamide (5 mg/kg) thus indicating only insulin stimulation as its mechanism of action (Table 1). Similar effects have been reported for the extracts of Parquetina nigrescens and Uvaria afzelii [26,31].…”
Section: Glucose Lowering Activity Of the Extractsupporting
confidence: 87%
“…They suggested that phytol and squalene isolated from the methanol leaf extract may be responsible for the improvement in the function of the kidney in diabetic mellitus possibly by increasing urea synthesis in urine metabolism and increasing the excretion of urea. Faloye and colleagues [ 50 ] conducted research on the methanol root bark extract of P. nigrescens and the convallatoxin compound isolated from P. nigrescens root bark. Administration of the methanolic root extract to streptozotocin-induced diabetic rats at a dose of 200 mg/kg body weight showed a significant dose and time-dependent reduction in blood glucose levels that was comparable to the standard control glibenclamide at 5 mg/kg for 4 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Singlet at δ 3.02 indicated single hydrogen (H-17) of C-17 of ring D, proving substitution at C-17 and singlet at δ 0.84 exposed 3 hydrogens of methyl group (C-18) attached to C-13. Double doublet at δ 4.72 and singlet at δ 5.59 were characteristic peaks for H-21 and H-22 of five membered lactone ring attached to steroid moiety (Faloye et al, 2018;McIntyre et al, 1990).…”
Section: Proton-nmr Spectrum Analysismentioning
confidence: 99%